2018
DOI: 10.1080/10903127.2018.1489017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Key Health and Wellness Indicators Among North Carolina Emergency Medical Service Providers

Abstract: These findings suggest a high prevalence of overweight and obesity, heavy drinking, binge drinking, and high BP among NC EMS personnel. Similar to fire service personnel, these rates are higher than the general US population. As such, they suggest areas where intervention would have the greatest positive impact on the health and performance of the EMS workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous work has shown that EMS personnel have a high prevalence of poor health for certain LS7 components such as obesity, poor diet, and inadequate physical activity. 7 , 8 , 9 EMS personnel also have a high prevalence of non‐traditional CVD risk factors, such as poor sleep quality, short or long sleep duration, and high stress, 10 , 11 , 12 , 13 which may further increase the risk of developing CVD. No prior studies have examined the relationship between sleep, stress, and CVH within the occupational group of EMS personnel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that EMS personnel have a high prevalence of poor health for certain LS7 components such as obesity, poor diet, and inadequate physical activity. 7 , 8 , 9 EMS personnel also have a high prevalence of non‐traditional CVD risk factors, such as poor sleep quality, short or long sleep duration, and high stress, 10 , 11 , 12 , 13 which may further increase the risk of developing CVD. No prior studies have examined the relationship between sleep, stress, and CVH within the occupational group of EMS personnel.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all EMS personnel work in a fire‐based setting, and their CVD risk remains unclear. Previous work has shown that EMS personnel have a high prevalence of poor health for certain LS7 components such as obesity, poor diet, and inadequate physical activity 7–9 . EMS personnel also have a high prevalence of non‐traditional CVD risk factors, such as poor sleep quality, short or long sleep duration, and high stress, 10–13 which may further increase the risk of developing CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Patient care also includes wellness. In this case, IoMT can leverage the periodic and continuous measurement and evaluation of wellness indicators [62,63]. Solutions include using smart thermometers capable of sharing essential data with medical applications [64].…”
Section: Internet Of Medical Things (Iomt) In Healthcarementioning
confidence: 99%